How Parents Instill Religious Education in Early Childhood - Mutia Angraini (Yayasan Adra Karima Hubbi, 2024)
This research is motivated by the importance of instilling religious education from an early age by parents, especially education in creed, morals, and worship. Religious education has begun to be embedded in children in Jorong Rumbai, this can be seen from there are children aged 3-4 years who have participated in reciting at TPA / TPQ, memorizing short letters, and participating in congregational prayers at mosques. This study aims to describe the way parents are, supporting factors, and obstacles in instilling creeds, morals, and worship in early childhood in Jorong Rumbai, South Batipuh District, Tanah Datar District. This study uses a type of qualitative research with phenomenal methods, the data sources used are primary data sources and secondary data. The results of this study show indicators of religious cultivation in early childhood, because busy so there is less time for children because they are too busy with cellphones so sometimes children become neglected, and family influence sometimes their older siblings who set a bad example. And also the influence of less educational viewing from television, cell phones, and so on. Based on the description above, it can be concluded that religious cultivation in early childhood in Jorong Rumbai is good, it's just that parents experience obstacles, for example from supporting media that are still inadequate. And constraints from the influence of parents, family, electronic media, gadgets, and the community environment.